1978
DOI: 10.1364/ao.17.000856
|View full text |Cite
|
Sign up to set email alerts
|

Laser isotope separation of rare earth elements

Abstract: The experimental results on the laser isotope separation of the neodimium, samarium, europium, gadolinium, dysprosium, and erbium by the selective two-step photoionization are given. The rare earth elements have been chosen for the investigation because they constitute a good series of the very similar but different atoms that are heavy enough and allow experiments to be carried out that are representative enough. The experimental technique developed for the laser isotope separation experiments has been applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The photo ionization wavelength threshold is given by λαSun1λnormalInormalP1λαprefix−1 where λ IP = 219.686 nm is the longest photon wavelength with enough energy to ionize atomic samarium assuming an ionization potential of I 1 = 45519.6 cm −1 (5.6437 eV). The photo ionization cross section is σ()λ={center00.25emnormalfnormalonormalr0.25emλ>λαSuncenterσnormalSnormalm0.25emnormalfnormalonormalr0.25emλλαSun0.5emwith0.5emσnormalSnormalm10prefix−21m2 based on the work of Karlov et al []. The photo ionization rate (or time) from level λ α is determined from kαSun=truetrue∫0λαSunFSun()λσ()λλhcnormaldλταprefix−1 where the spectrum of the solar flux F Sun has been previously shown in Figure .…”
Section: Samarium (Sm+) Ions Produced By Photo Ionization From Sm Metmentioning
confidence: 99%
See 1 more Smart Citation
“…The photo ionization wavelength threshold is given by λαSun1λnormalInormalP1λαprefix−1 where λ IP = 219.686 nm is the longest photon wavelength with enough energy to ionize atomic samarium assuming an ionization potential of I 1 = 45519.6 cm −1 (5.6437 eV). The photo ionization cross section is σ()λ={center00.25emnormalfnormalonormalr0.25emλ>λαSuncenterσnormalSnormalm0.25emnormalfnormalonormalr0.25emλλαSun0.5emwith0.5emσnormalSnormalm10prefix−21m2 based on the work of Karlov et al []. The photo ionization rate (or time) from level λ α is determined from kαSun=truetrue∫0λαSunFSun()λσ()λλhcnormaldλταprefix−1 where the spectrum of the solar flux F Sun has been previously shown in Figure .…”
Section: Samarium (Sm+) Ions Produced By Photo Ionization From Sm Metmentioning
confidence: 99%
“…based on the work of Karlov et al [1978]. The photo ionization rate (or time) from level λ α is determined from…”
Section: Samarium (Sm + ) Ions Produced By Photo Ionization From Sm Mmentioning
confidence: 99%
“…The selective photoionization technique for isotope isolation of Nd, Sm, Eu, Gd, Dy, Er, Li, U, etc. was shown by Karlov et al [ 77 ] Resonance‐based diode laser ionization of lithium isotopes was reported by Olivares et al, [ 78 ] where the lithium isotopes were isolated using the ultranarrow‐width laser with tuning capability along with the fine structure levels at 2 p . A 47% increase in 6 Li concentration using a two‐step laser ionization via the time‐of‐flight (TOF) mass spectrophotometer was recorded by Saleem et al [ 79,80 ] Additional isotope selectivity for achieving greater isotope enrichment can be given by the TOF mass spectrophotometer.…”
Section: Laser Methodsmentioning
confidence: 99%
“…Coherent laser sources have wide applications in spectroscopy, lithography, and photochemical process [1][2][3]. In particular, such kind lasers with narrow linewidth and high power are more attractive in fine precision spectroscopy, optical pumping, and laser isotope separation [4][5][6]. Conventional dye lasers have been used as the primary sources in visible and near-IR range because of their excellent tunable ability, but the disadvantages such as poor beam quality, degradation with time, toxic chemicals, complex recycle system, and expensive cost restrict their further development.…”
Section: Introductionmentioning
confidence: 99%